Professional Identities and the Watershed of War: Teachers, Histories and Memories - Cunningham, Peter James (Historia y Memoria de la Educación, 2015)
Teachers’ individual lives and careers, identities and experiences are so various as to almost defy generalization. A valid and realistic aim of educational research is however to identify significant commonalities that enhance an understanding of the teacher’s role. Memory is a prime resource for investigating factors that change over time in the course of a career and oral history provides a means of accessing and interpreting such a rich vein of evidence. One common feature shared by teachers in Britain during the mid-twentieth century was the impact on schooling of total war. This paper draws on the memories of three teachers interviewed during a large-scale enquiry into British teachers whose careers spanned World War II. Analysis of this evidence is made with reference to recent writings on professional identity, and one aim of the paper is to promote continuing reflection on the way teachers’ identities develop under the constraints of changing historical circumstance. Testimony selected for discussion here concerns their early education and career choices, their initial teacher training and their continuing professional formation, punctured for each at different points by the single overwhelming historical event of war. The paper concludes with reference to recent literature on teacher identity, indicating how historical research and autobiographical perspectives across a whole career can contribute to contemporary understandings of how teachers perceive their work, and the formation of professional identities.